Network and parallel computing : 13th IFIP WG 10.3 International Conference, NPC 2016, Xi'an, China, October 28-29, 2016, proceedings /: 13th IFIP WG 10.3 International Conference, NPC 2016, Xi'an, China, October 28-29, 2016, proceedings. (2016) - Unknown
No abstract available